2011
DOI: 10.1007/s12560-011-9053-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Activity of Alcohol-Based Handrubs Against Human Noroviruses Using the Fingerpad Method and Quantitative Real-Time PCR

Abstract: Noroviruses (NoV) are the most common cause of acute nonbacterial gastroenteritis in the United States, and human hands play an important role in their transmission. Little is known about the efficacy of hand hygiene agents against these highly infectious pathogens. We investigated the activity of seven commercially available hand hygiene products against human noroviruses by in vivo fingerpad tests. The in vivo activity of alcohol-based handrubs ranged from 0.10 to 3.74 log reduction and was not solely depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…These findings are consistent with previous findings that the in vivo activity of ABHRs is not solely dependent upon alcohol concentration (12,24,28). In a previous study, the 70% EtOH AF gel provided significantly greater HNV reduction than did other hand hygiene products that contained >85% ethanol (24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with previous findings that the in vivo activity of ABHRs is not solely dependent upon alcohol concentration (12,24,28). In a previous study, the 70% EtOH AF gel provided significantly greater HNV reduction than did other hand hygiene products that contained >85% ethanol (24).…”
Section: Discussionsupporting
confidence: 92%
“…Typical ABHR activity against nonenveloped enteric viruses varies depending on the type and concentration of alcohol (5, 6,14,21). Different strains of HNVs may be more resistant to antimicrobial agents than others (24). Several studies have been conducted on newly formulated ABHRs with significantly improved inactivation of nonenveloped vimses (24, 28).…”
mentioning
confidence: 99%
“…Ethanol was determined to be ineffective against NoV even at concentrations !90% alcohol (53,100). However, hand sanitizers containing ethanol in combination with other compounds could be effective in reducing NoV (51). Hands (finger pads) rinsed for 10 s with water alone reduced NoV levels by up to 1.58 log, which was better than for finger pads washed with antibacterial soap containing 0.5% triclosan or an alcohol-based hand sanitizer (53).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we directly compared RT-qPCR and infectivity data from surrogates to hNoV RT-qPCR data for key treatments (excluding studies that reported on surrogates alone or hNoV RT-qPCR data alone). Data were extracted NASBA Nowak et al (2011b) Disinfectants and sanitizers in solution hNoV RT-qPCR data only Liu et al (2010) Liquid soap and hand sanitizers on contaminated hands hNoV RT-qPCR data only Liu et al (2011) Alcohol based hand rubs hNoV RT-qPCR data only Mormann et al (2010) Reduction in RT-qPCR signals following food processing conditions hNoV RT-qPCR data only Ngazoa et al (2008) Attachment to stainless steel and household disinfection hNoV RT-qPCR data only Richards et al (2012) Freezing and thawing and capsid integrity hNoV RT-qPCR data only D' Souza et al (2006) Persistence on stainless steel, ceramic and formica and transfer to lettuce Qualitative RT-PCR Hudson et al (2007) Ozone fog disinfection of surfaces Qualitative RT-PCR Barker et al (2004) Cleaning and decontamination study Qualitative RT-PCR Bertrand et al (2012) Review paper Avoidance of duplication Kitajima et al (2010) Chlorine inactivation in water. hNoV data was limited by the scale of the study.…”
Section: Discussionmentioning
confidence: 99%